Nivel de conocimiento y aceptación sobre sellado dentinario inmediato en preparaciones dentarias para restauraciones indirectas de cirujanos dentistas, Trujillo-2022 - Montalvo Aquino, Fany Alejandra (2022)
The objective of this research is to publicize the level of knowledge that Trujillo dentists have about immediate dentin sealing and acceptance in their professional practice. It is a descriptive, cross sectional study in which an asynchronous virtual survey was carried out, the sample studied was made up of 178 dental surgeons from the province of Trujillo out of a total of 1920 surgeons.It can be distinguished that of the total of dental surgeons with less work experience, 65.8% perceive a poor level of knowledge, while surgeons with more years of service are above 80% (p <0.05). Regarding the level of acceptance, the majority (51.7%) perceives that they totally agree with performing the operative technique.It can be concluded that there is a significant statistical difference between the level of knowledge of dental surgeons in the province of Trujillo about immediate dentin sealing according to the years of work experience. It can be distinguished that those surgeons with experience ≤ 5 years can report better levels, even when the values obtained on a good level of knowledge are well below the desired level.